2019
DOI: 10.3390/su11071952
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Decision Making for Sustainability and Value Assessment in Early PSS Design

Abstract: Sustainability is increasingly recognized as a key innovation capability in the organization. However, it is not always evident for manufacturers how sustainability targets shall be “mixed and matched” with more traditional objectives—such as quality, time, cost, and performances—when designing and developing solutions. The emergence of “servitization” and product-service systems (PSS) further emphasizes the need for making thoughtful trade-offs between technical aspects, business strategies, and environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 114 publications
0
38
0
5
Order By: Relevance
“…Kwok et al [69] include socio-ecological sustainability indicators covering a product life-cycle, which are derived systematically from a product sustainability design space [70]. This approach has its strength in that it is based on a backcasting approach from scientific scrutinized overarching sustainability principles [27], in comparison to other models that have criteria identified from a forecasting and ad hoc approach, e.g., suggested in Bertoni [71].…”
Section: Number Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwok et al [69] include socio-ecological sustainability indicators covering a product life-cycle, which are derived systematically from a product sustainability design space [70]. This approach has its strength in that it is based on a backcasting approach from scientific scrutinized overarching sustainability principles [27], in comparison to other models that have criteria identified from a forecasting and ad hoc approach, e.g., suggested in Bertoni [71].…”
Section: Number Of Articlesmentioning
confidence: 99%
“…At the same time, the industry sees a need for the authorities to express clearly what is required. In a recent study [71], an expert group from the manufacturing industry suggested that business models are established on a national level to accelerate adaption and implementation of more sustainable products and services. In this way, social institutions and industry can meet the future goals together.…”
Section: Drivers To Develop Within the Three Areasmentioning
confidence: 99%
“…To construct an index, the underlying model should be clearly defined so that the formulation strategy for normalization, weighting, and aggregation techniques can be determined [10]. In this regard, multicriteria decision-making (MCDM) methods provide promising opportunities to deal with the multidimensional and complex nature of sustainability [20]. MCDM refers to a set of methods to be used for supporting decision-making in a multicriteria environment by analyzing a series of possible alternatives [21,22].…”
Section: Prosmentioning
confidence: 99%
“…In the literature, numerous studies have investigated the application of PSSs in different industrial contexts [30,31], providing PSS models and tools to support manufacturers in the implementation of integrated solutions [32,33]. In particular, a large number of studies have focused on the Use-Oriented PSSs (i.e., when the company provides the product's functions rather than the ownership of the product), since the manufacturer's interventions to optimize the use phase of the product can be very beneficial not only for the PSS stakeholders but also in terms of environmental performances [34,35].…”
mentioning
confidence: 99%
“…Accordingly, the use of supporting methods has not been discussed in detail. In fact, a further investigation on the application of tools for facilitating both the analysis of PSS components (e.g., The Quality Function Deployment for PSS and the Axiomatic Design methods [33,94]), as well as the interoperability between the various actors (e.g., CMMS [95] and COBIE [96,97] tools) is necessary.…”
mentioning
confidence: 99%